The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1590/s0104-11692007000100006
|View full text |Cite
|
Sign up to set email alerts
|

Humanizing care through the valuation of the human being: resignification of values and principles by health professionals

Abstract: HUMANIZANDO EL CUIDADO A TRAVÉS DE LA VALORIZACIÓN DEL SER HUMANO: RESIGNIFICACIÓN DE LOS VALORES Y PRINCIPIOS POR LOS PROFESIONALES DE SALUD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 5 publications
3
9
0
11
Order By: Relevance
“…This is in line with the work of Stein-Backes, Santos Koerich, and Lorenzini Erdmann, [50] which indicated that humanization had positive effects on work conditions, socioprofessional relationships, and loyalty among health professionals. Likewise, our results corroborate several authors' work on humanistic approach in nursing administration, [51][52][53][54][55][56][57][58][59] mentioning that harmony and transparency in relationships between colleagues are characteristics of primary importance that go a long way towards improving life at work.…”
Section: Contextual Elements Conducive To the Humanizationsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in line with the work of Stein-Backes, Santos Koerich, and Lorenzini Erdmann, [50] which indicated that humanization had positive effects on work conditions, socioprofessional relationships, and loyalty among health professionals. Likewise, our results corroborate several authors' work on humanistic approach in nursing administration, [51][52][53][54][55][56][57][58][59] mentioning that harmony and transparency in relationships between colleagues are characteristics of primary importance that go a long way towards improving life at work.…”
Section: Contextual Elements Conducive To the Humanizationsupporting
confidence: 87%
“…To our knowledge, there is an urgent need to invest economically in creating a humanistic work environment that facilitates the adaptation of NMs and their personal and professional development as they transition to management practices based on caring attitudes and values (e.g., compassion, gentleness, mutual respect). [49,50,[52][53][54][55][56][57] As professionals, nurse executives and administrators can make caring the norm and can help attain the dual goal of fiscal responsibility and optimal patient care. [58] Some of our findings enrich the existing knowledge found in the literature, while innovative results add to the body of knowledge related to the advancement of nursing management.…”
Section: Implications For Nursing Managementmentioning
confidence: 99%
“…The present results agree with those of previous studies (18)(19)(20) , which have shown the possibilities of developing new competencies for health care, capable of assigning new meanings to nursing practice, allying technical-scientific and human competence with a view to the humanization of a health care process that considers both patients and health care workers.…”
Section: Final Considerationssupporting
confidence: 92%
“…It is believed that, similar to other studies (20)(21) on this theme, this research can collaborate to to the health needs of the user. Finally, it is essential that nurses develop a profile of competences for this educational activity (22) , in which the objective is to contribute to increase users' care autonomy and capacity, also increasing their responsibility for their own health.…”
Section: Final Considerationssupporting
confidence: 68%